PELATIHAN DIGITAL MARKETING BAGI PELAKU UMKM DI PAROKI ARNOLDUS JANSEN BEKASI - Wawa Santoso; Denta Felli Ananda; Nila Pusvikasari; Nuno Sutrisno (LPPM Universitas Bina Bangsa, 2024)
Digital marketing training provided to MSME activists (Micro, Small and Medium Enterprises) under the auspices of the Socio-Economic Development Section (PSE) of the Small Business Guidance Center (SABUK) team within the Catholic Church of St. Arnoldus Jansen Parish Bekasi aims to increase awareness and utilization of digital marketing media to develop businesses. Activities are carried out through material presentation, discussion and question and answer as well as direct practice on the use of WA business, market place and simple photography techniques through smart phones. This activity was carried out directly in the Parish hall, with participants of around 100 people from various business backgrounds and took place from 09.00-15.00 WIB smoothly where participants followed this activity enthusiastically. Thus, this activity is very important for the use of digital marketing facilities by MSME actors in the parish environment. This activity will be followed up with other relevant training materials at the next meeting session